2022
DOI: 10.6018/cpd.482241
|View full text |Cite
|
Sign up to set email alerts
|

The relative age effect on the selection of young athletes and the performance of Brazilian futsal teams

Abstract: Objetivo: El objetivo del presente estudio es evaluar el efecto de la edad relativa en la selección de los atletas jóvenes y el rendimiento de los equipos de fútbol sala. Métodos: Se recopiló la fecha de nacimiento de 2.676 jóvenes atletas (femeninos: n=292; masculinos=2.384) que jugaban en las categorías Sub-9 a Sub-20 de fútbol sala brasileño. Los atletas fueron categorizados en base al cuartil y al semestre de nacimiento. La posición final de los equipos en el torneo fue categorizada como finalista, semifin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Similarly, it has been reported in the scientific literature that team sports, among which soccer and basketball stand out, present a greater number of investigations about volleyball and handball in the study RAE (Fonseca, Figueiredo, Gantois, Lima-Junior & Fortes, 2019;. In that sense, a tendency towards the selection of athletes born in the first months of the year is presented for male teams, although this effect was not observed in female teams (Papadopoulou et al, 2019;Leonardi et al, 2022). On the other hand, another study developed by Saavedra- sought to assess whether the RAE remains present throughout the history of FIBA basketball world championships in the lower categories, determining that it not only decreases over time (as occurs in the male U19 category), but for the female U19 category, it increases.…”
Section: Introductionsupporting
confidence: 60%
“…Similarly, it has been reported in the scientific literature that team sports, among which soccer and basketball stand out, present a greater number of investigations about volleyball and handball in the study RAE (Fonseca, Figueiredo, Gantois, Lima-Junior & Fortes, 2019;. In that sense, a tendency towards the selection of athletes born in the first months of the year is presented for male teams, although this effect was not observed in female teams (Papadopoulou et al, 2019;Leonardi et al, 2022). On the other hand, another study developed by Saavedra- sought to assess whether the RAE remains present throughout the history of FIBA basketball world championships in the lower categories, determining that it not only decreases over time (as occurs in the male U19 category), but for the female U19 category, it increases.…”
Section: Introductionsupporting
confidence: 60%
“…Specifically, in futsal, Perondi et al (2018) did not observe RAE in 410 athletes from an adult female competition in Brazil. Leonardi et al (2022) also found no effects of RAE in 292 female futsal players aged 15 to 20, considering the teams' final classification. Our results reinforce these findings in female futsal, but now in the context of one of the most important Brazilian competitions.…”
Section: Discussionmentioning
confidence: 79%
“…Accordingly, futsal is more practiced by men in Brazil (data made available by CBFS on April 27, 2023: 356,831 male and 36,915 female athletes registered), and the sport is not as popular for females, which may reduce the competition for spots in teams and cause a reduction in the RAE likelihood. Indeed, Leonardi et al (2022) investigated 140 male futsal teams aged between 9 and 20 years, while in the same study, only 19 female futsal teams were found, between 15 and 20 years, highlighting that the female practice of the sport modality is reduced. Another relevant aspect is the fact that in Brazil, women's futsal competitions start at later age, after 13 years old (Perondi, et al, 2018), which can lead to a later specialization in girls when compared to boys.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations